PENGARUH BUKU AJAR BERMUATAN KECERDASAN KOMPREHENSIF DALAM MODEL PEMBELAJARAN INKUIRI TERHADAP KOMPETENSI PESERTA DIDIK KELAS X SMAN 5 PADANG - Faradillah Faradillah; Asrizal Asrizal; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2017)
Holistic competencies of learner are important in 2013 curriculum for all subject. But holistic competencies aren’t implemented in physics learning proccess in high school yet. As solution of this problem is to implement learning textbook by integrating comprehensive intelligence in inquiry model. The objective of this research is to investigate the difference competence of students and to investigate the effect of learning textbook by integrating comprehensive intelligence. The type of this research is quasy experiment with randomized control group only design. As population of this research is all learner grade X in SMAN 5 Padang that leasted in 2016/2017 years. Sampling technique in this research is purposive sampling. There are three instruments in this research, those are test sheet, observation sheet, and performance sheet. Data are analized by descriptive statistic, compare mean test, linear regresion, and corelation analysis. There are two of  research results. First, implementation of learning textbook by integrating comprehensive intelligence in Iinquiry model has given significant difference competece of learners including knowledge, spiritual, social and emotional, and skills competence. Second, implementation of learning textbook by integrating comprehensive intelligence in inquiry model has given significant effect to improve knowledge, spiritual, emotional and social, and skills competences of learner respectly 21.16 %, 30.02 %, 12.38 %, and 30.02%